2022
DOI: 10.1001/jamaoncol.2022.4319
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prostate-Specific Antigen Screening Rates With Subsequent Metastatic Prostate Cancer Incidence at US Veterans Health Administration Facilities

Abstract: ImportanceThere is controversy about the benefit of prostate-specific antigen (PSA) screening. Prostate-specific antigen screening rates have decreased since 2008 in the US, and the incidence of metastatic prostate cancer has increased. However, there is no direct epidemiologic evidence of a correlation between population PSA screening rates and subsequent metastatic prostate cancer rates.ObjectiveTo assess whether facility-level variation in PSA screening rates is associated with subsequent facility-level met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This case series demonstrated that prostate cancer occurs in transgender women and is not as rare as published case reports might suggest. However, rates were lower than expected based on prior prostate cancer incidence estimates in cisgender male veterans . Using data from 2005 to 2019, the age-weighted cisgender mean number of cases was 331 per 100 000 in 2011 (median year of transgender identity entry in the VA).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This case series demonstrated that prostate cancer occurs in transgender women and is not as rare as published case reports might suggest. However, rates were lower than expected based on prior prostate cancer incidence estimates in cisgender male veterans . Using data from 2005 to 2019, the age-weighted cisgender mean number of cases was 331 per 100 000 in 2011 (median year of transgender identity entry in the VA).…”
Section: Discussionmentioning
confidence: 71%
“…However, rates were lower than expected based on prior prostate cancer incidence estimates in cisgender male veterans . Using data from 2005 to 2019, the age-weighted cisgender mean number of cases was 331 per 100 000 in 2011 (median year of transgender identity entry in the VA). Given estimates of 10 000 transgender women in the VA, 33 cases per year would be expected.…”
Section: Discussionmentioning
confidence: 71%
“…[7][8][9] Based on this uncertain benefit-to-harm ratio, trends in practice away from screening have resulted in a rising incidence of incurable, metastatic prostate cancer for the first time in decades. 14,44 Despite a clinical capacity to detect and effectively treat prostate cancer that is uniquely high among prevalent malignancies, the lack of a practical, highly accurate, and well-defined diagnostic approach in men with elevated serum PSA has impeded progress against the disease, which remains a leading cause of morbidity and mortality worldwide. Ultimately, there is an extraordinary need for a reliable clinical test to reduce the harms associated with prostate cancer screening and preserve its known mortality benefits.…”
Section: Discussionmentioning
confidence: 99%
“…MOFs have shown great promise in a variety of applications including biomineralization, encapsulation, chemical sensors, vaccines, , gas storage, catalysis, and small molecule drug delivery such as doxorubicin and methylprednisolone. In the latter, zeolitic imidazolate framework (ZIF)-90 was found to be more efficient than ZIF-8 at delivery in vivo for methylprednisolone. MOFs also exhibit exceptional thermal stability and the long shelf life of precursor materials, which can be readily deployed in various resource-limited settings. Their ability to readily encapsulate biomolecules and release drugs in response to various (bio)­chemical stimuli renders ZIFs, a class of MOFs, attractive for a wide range of biomedical applications. In previous studies, we successfully encapsulated a wide range of proteins in urine and plasma using ZIF-8 as the encapsulate. In those studies, we examined the MOF encapsulation of one biomarker at a time. Here, we not only extend these studies specifically to prostate-specific antigen (PSA) but also measure the ability of ZIF-8 (composed of a hydrophobic organic linker) and ZIF-90 (composed of a hydrophilic organic linker) to preserve a broad range of biomarker proteins in patient plasma for MOF-based biopreservation and eventual on-demand reconstitution and analysis.…”
Section: Introductionmentioning
confidence: 99%